PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN NASABAH UNTUK MENJADI DEBITUR PADA BANK SYARIAH MANDIRI KCP ANTAPANI BANDUNG - Jujun Jamaludin (Jurnal Maps (Manajemen Perbankan Syariah), 2017)
This research is motivated by the emergency of bank that resulted in competition, Sharia bank must implement a good marketing strategy if it wants to survive and competitive. So that Mandiri Sharia Bank by providing quality service and promotion in inancing product is expected to increase the number of customers thus provide greater profits for the bank. In fect the number of customersfinacing in Mandiri Sharia Bank KCP Antapani Bandung during the last year from 2012 to 2014 amounted to only 111 customer financing. Whereas for 3 years is targeted to reach 360 customers. Thus the fact that only 30.83 % are achieved by Mandiri Sharia Bank KCP Antapani Bandung of the targeted amount.This phenomenon that makes the rationale for this study that assumes there is a correlation between quality of service and promotion to the purchasing dicision. By the research hypothesis quality service (X1) and promotion (X2)) significantly influence the customer’s decision (Y) to be debtors in Mandiri Sharia Bank KCP Antapani Bandung for the targeted amount. The theory used in this study is the marketing management of services quality, promotion and purchasing decision. The purpose of this study was to determine how much influence of quality service (X1) and promotion (X2)) significantly influence the customer’s decision (Y) to be debtors in Mandiri Sharia Bank KCP Antapani Bandung.This research included in explanatory research and included in quantitative research with survey method. The sampling is using random sampling techniques. From 111 customer financing in Mandiri Sharia Bank KCP Antapani Bandung (population) 87 customers have chosen as respondets (sample). Then to know the influence of qua;ity service and promotion to customer’s decision by testing the hypothesis by doing comparison between t table with t count (t and F test). And to determine the effect of each influence X1 and X2)  to Y then performed multiple linear regression analysis calculation using the program tools IBM SPSS 22,0.The conclusions based on research rsults can be known thar service quality has significant influences to the customer’s decision amounted to 45.0% and promotion signifanct influence to the customer’s decision amounted to 17.6%. then simultaneously, the quality of service and promotion has significant influence to the cutomer’s decision amounted to 62.6%. while the remaining 37.4% is influenced by other variables that not examined.